STUDI CROSS SECTIONAL TERHADAP HUBUNGAN ASUPAN PROTEIN DENGAN KADAR PROTEIN TOTAL ASI PADA IBU MENYUSUI - Marissa, Febi Marissa; Flora, Rostika; Zulkarnain, Mohammad; Ermi, Nurmalia; Jasmine, Annisah Biancika; Aguscik, Aguscik; Ikhsan, Ikhsan; Slamet, Samwilson; Purnama, Yetti; Sulung, Neshy (LPPM STIKES BHAKTI HUSADA BENGKULU, 2023)
Background: During breastfeeding, mothers need adequate nutritional intake, including protein intake. Essential amino acids play an important role in the process of breast milk protein synthesis and can increase the production and protein of breast milk. Breast milk protein is needed to support the growth and development of infants in the early stages of life. This study aims to analyze the relationship between protein intake and breast milk protein levels in breastfeeding mothers. Methods: This study was a quantitative study with a cross-sectional approach conducted in Seluma Regency. The sample used was 77 breastfeeding mothers aged 20-35 years who were randomly selected. Protein intake was obtained using 3x24 hour food recall, then calculated using the Nutri survey application. Breast milk protein levels were measured using the spectrophotometric method. Characteristic data were obtained through interviews. The data obtained were then processed and analyzed using univariate and bivariate analysis using SPSS version 20. Result: The measurement of protein intake showed that 76.6% of breastfeeding mothers had insufficient protein intake. Measurement of breast milk protein levels showed that 67.5% of breastfeeding mothers had insufficient breast milk protein levels. Statistical test results showed that there was a significant relationship between protein intake and breast milk protein levels in breastfeeding mothers (p=0.007; PR=1.961; CI=1.08-3.56). Mothers who have less protein intake have a 1.96 times greater risk of having low breast milk protein levels. Conclusion: There is a significant relationship between protein intake and breast milk protein levels in breastfeeding mothers (p<0.005). Education related to protein intake in breastfeeding mothers needs to be done. Adequate protein intake can produce the needed quality of breast milk to help the optimal growth and development of the baby.Key words: breast milk, breast milk, protein intake, breastfeeding mothers, milk protein levels